Livestock market of Palangki (1996 – 2017): a study of socio-economic history - Felia Siska; Siti Fatimah; BuchariNurdin (International Conferences on Educational, Social Sciences and Technology)
Livestock Market of Palangki is included in Type A’s regional livestock markets and categorized as the largest in Central Sumatra. This market has its own uniqueness especially its transactional activity which is also known as “Marosok”. This paper was aimed to unveil the secret behind its presistence, until now. This study used a historical method. The result showed that Toke who did transaction in the market were not only from West Sumatera but many of them were also from outside of West Sumatera. Livestock market of Palangki has been surviving until today due to government’s role, marketing network between Toke ternak, market security and its strategic location.